2006
DOI: 10.1038/sj.ejcn.1602501
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake in asylum seeker children in The Netherlands, strongly related to age and origin

Abstract: Objective: To monitor the dietary intake of energy, macro-and micronutrients in asylum seeker children. Design and setting: Cross-sectional study in three asylum seeker centres in The Netherlands. Subjects: Hundred and sixteen children 2-12 years old (86% of the study cohort) provided a dietary history. Method: The dietary intake was estimated by 24 h recall, and the origin of the children was classified in three geographic regions: African (n ¼ 45), Central Asia (n ¼ 34) or Eastern Europe (n ¼ 37). Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We recently demonstrated that asylum seekers' children in the Netherlands frequently have low dietary iron intake (9). However, it has remained unclear to what extent iron status of asylum seekers' children is compromised during their stay in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that asylum seekers' children in the Netherlands frequently have low dietary iron intake (9). However, it has remained unclear to what extent iron status of asylum seekers' children is compromised during their stay in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%